Insights into pituitary stalk interruption syndrome: 2 cases that illuminate the condition - Fadwa Jaheddine; Nazik Allali; Siham El Haddad; Latifa Chat (Radiology Case Reports)
Pituitary stalk interruption syndrome (PSIS) is a congenital anatomical defect that leads to pituitary insufficiency, The symptoms are diverse, often leading to diagnostic delays or even misdiagnosis. MRI plays a crucial role in establishing an accurate diagnosis by revealing a characteristic radiological triad: a thin or absent pituitary stalk, an ectopic or missing posterior pituitary gland, and anterior pituitary hypoplasia. We herein describe 2 cases: 1 involving a 9-year-old boy and the other an 11-year-old girl, both diagnosed with PSIS.